Migration and Health—Freedom of Movement and Social Benefits for Chinese Migrant Workers - Fengxian Qiu (MDPI AG, 2021)
This study utilized the concept of social right to understand factors affecting migrant workers’ health and healthcare in China. Using mixed methods, this study integrated findings from a survey of 817 migrant workers and a follow-up study of 30 intensive interviews to present an in-depth understanding of cumulative disadvantage of health and healthcare of rural-to-urban migrant workers. Our quantitative results indicated that migrant workers with no more than 5 years of working experience and having a good relationship with employers were 65% and 72.8% more likely to report good self-rated health as compared to their counterparts; those with work-related injury experience and low income were 41.6% and 53.6% less likely to report good self-rated health. Qualitative findings revealed the social contexts of the cumulative effect of the length of work experience and fear of medical cost on migrant workers’ declining health. Even though the participation rate for health insurance in China is reported to be over 99%, the lack of portability in health insurance and different reimbursement rates in health care access are structural barriers in health-seeking behaviors among Chinese migrant workers and in establishing sustainability in China’s healthcare system. This study adds to the literature by delineating the process of the unequal access to social rights in general, healthcare in particular as the major explanation for migrant workers’ poor health beyond the surface of China’s universal healthcare.